Estabelecimento in vitro de marmeleiro japonês (Chaenomeles sinensis Koehne) CV andramig - Figueiredo, Geórgea Soares (2009)
The Japanese quince (Chaenomeles sinensis Koehne) can be used as rootstocks for quince, pear, loquat trees and as cultivar canopy. The use of quince by seeds, as rootstocks for other quince species and cultivars, has been shown viable. However, the inconvenient in the sexual reproduction is obtaining of not uniform seedlings, since it is not desired in the commercial plantations establishment due gene segregation. The seedlings production technology for Japanese quince by vegetative propagation is not defined, due low percentage of rooting. Thus, the tissue culture presents as a viable alternative in the clonal orchards development or seedlings commercial production. Experiments were performed to determine a protocol of in vitro establishment this specie, where was tested the disinfectant with chlorine appropriate for vegetal material, as well as cytokinin, flask cover, salt concentration of culture medium, culture medium, BAP cytokinin concentration and light quality. It could be conclude that calcium hypochlorite disinfectant is effective in the explants disinfestations, and the BAP provides better results in the establishment than 2iP and Zea cytokinins. Sealed flasks with cotton instead aluminum, reduce the explant oxidation and the original salt concentration of MS medium promotes better explant establishment. The WPM medium showed higher results than MS medium and BAP at 1mg.L-1 or 2mg.L-1 concentration promotes an increase in the number and length of sprouting, as well as the use of red light instead white and green light.